Myoepithelial carcinoma of soft tissue is a diagnostic challenge on fine‐needle aspiration: Case report and review of literature. Issue 7 (28th February 2022) - Wang, Lucy; Yee‐Chang, Melissa; Sun, Wei; Melamed, Jonathan; Simsir, Aylin; Shi, Yan
Abstract: Myoepithelial carcinoma (MEC) of soft tissue, also known as malignant myoepithelial tumor, is an uncommon malignancy. Cytologic diagnosis of this entity is challenging due to its rarity and heterogeneous morphology. We report a case of MEC in a 22‐year‐old man, who presented with a 6.5 cm soft tissue mass on his right distal forearm that has been enlarging over the past 3 months. Ultrasound‐guided fine‐needle aspiration (FNA) revealed abundant isolated neoplastic cells ranging from spindled cells to epithelioid and plasmacytoid morphology in a myxoid background. These cells showed moderate cytologic atypia characterized by high‐nuclear/cytoplasmic ratio, irregular nuclear contours, and prominent nucleoli. The cytoplasm varied from dense to vacuolated and occasionally rhabdoid with intracytoplasmic inclusions. Scattered bi‐ and multinucleated cells were identified. A diagnosis of high‐grade malignancy was made with the differential diagnosis including rhabdomyosarcoma and melanoma. A subsequent core biopsy of the tumor showed immunoreactivity for pan‐cytokeratins, calponin, p63, and smooth muscle actin. INI‐1 was lost. SOX‐10 and Melan‐A were negative. Molecular studies showed loss of SMARCB1 (INI‐1) and CDKN2A . Gene fusion studies did not detect any fusion. A diagnosis of soft tissue MEC was made which is a challenge on FNA due to several cytologic mimickers including rhabdomyosarcoma, epithelioid sarcoma, extrarenal rhabdoid tumor, extra‐axial chordoma and melanoma. Recognition of the biphasic cell population in a myxoid background and a battery of immunohistochemical stains are crucial for accurate diagnosis.